Performance measurement in Malaysian container haulage industry : A critical evaluation - Mohd. Zaid, Zailani; Shah, Muhammad Zaly (2007)
Evaluating operational performance is one of the most critical business activities as it helps organisations measure their competitiveness level. Knowing current performance level helps managers strategise what should be done to stay ahead of the competition as well as increase market presence. In this paper, the methods the container haulage industry in Malaysia used to measure their operational performance are critically evaluated. Based on primary data obtained from major players in the haulage industry, there is a lack of common benchmark for these haulage operators could use to measure industry performance. Instead, each haulage operators use their own performance measures which basically are simple input-output production ratios. Therefore, this paper proposes that a common performance measure is adopted as industry benchmark. The benefit of this common performance measure is the ability to identify the most efficient haulage operator with which other haulage players can benchmark.